PENGGUNAAN BERBAGAI JENIS MULSA DAN DOSIS PUPUK KASCING TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PARE (Momordica charantia. L) - Suhendra Suhendra; T Rosmawaty; Zulkifli Zulkifli (DINAMIKA PERTANIAN, 2015)
The purpose of this research was to examinee the effect of using various types mulch and dosage intereactinally and inddividully on growth and production of pare. The research was conducted at the experimental farm of Faculty of Agriculture Riau Islamic university during 4 months, starting from March to June 2014. The completely randomized design was used by using 2 factors. The first factor was M (various tyes of mulch), consisting of M0 (without mulch), M1 (black plastic mulch), M2 (oil palm leaf mulch), and M3 (alang-alang mulch). The second factor was K (Kascing fertilizer), consisting of K0 (0 g/plot), K1 (360g/plot), K2 (720 g/plot), and K3 (1,080 g/plot). The observed parameters were flowering age, harvested age, number of fruit per plot, weight fruit per plot, and number of fruit residue per plot. The results showed that the using of various types of mulch dan kascing fertilizer dosage interactionally had no a significantly effect on all observed parameters. However, the using of various mulchs affected significantly on all observed parameters with the best treatment of using black plastic mulch. The sgnificant effct was found on using kascing ferlizer dosage for all observed parameter with the best treatment of using 1.080 g/plot.